Mucha Ozerov and Ortalischema Frey newly recorded from China with descriptions of two new species (Diptera, Sepsidae) - Li, Xuankun; Yang, Ding (Zootaxa, 2014)
Eleven genera and 55 species of Sepsidae were known to occur in China. Here two genera, Mucha Ozerov and Ortalischema Frey, are newly reported from China with the following two new species: Mucha liangi sp. nov. and M. yunnanensis sp. nov. Two species, Mucha tzokotucha and Ortalischema maritima, are newly recorded from China. Thus, there are a total of 13 genera of Sepsidae distributed in China. A key to the species of Mucha and a key to the Chinese genera of Sepsidae are provided.